Application of Mckinsey's 7s Model in Increasing Profitability at PT BPRS Karya Mugi Sentosa Surabaya - Bahrul Hikam, Muhammad; Iqbal Pratikto, Muhammad (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research discusses the application of McKinsey's 7S model in increasing profitability at PT BPRS Karya Mugi Sentosa Surabaya. McKinsey's 7S model consists of seven main elements: strategy, organizational structure, operational system, leadership style, staffing, skills, and shared values. The research used a qualitative approach with direct observation methods, structured interviews, and in-depth data analysis to evaluate the effectiveness of the model. The results showed that the harmonization of the elements of McKinsey's 7S model contributed significantly to improving profitability, reflected in the increase in assets, growth in the number of customers, and stability of financial statements over the past five years. However, challenges such as HR adaptation to the new strategy and consistency of implementation are concerns that need to be addressed. This study concludes that the implementation of McKinsey's 7S model is able to encourage the strengthening of corporate strategy and competitiveness in the midst of intense competition in Islamic banking.